2017
DOI: 10.1080/21541248.2017.1356432
|View full text |Cite
|
Sign up to set email alerts
|

Impairments in age-dependent ubiquitin proteostasis and structural integrity of selective neurons by uncoupling Ran GTPase from the Ran-binding domain 3 of Ranbp2 and identification of novel mitochondrial isoforms of ubiquitin-conjugating enzyme E2I (ubc9) and Ranbp2

Abstract: The Ran-binding protein 2 (Ranbp2/Nup358) is a cytoplasmic and peripheral nucleoporin comprised of 4 Ran-GTP-binding domains (RBDs) that are interspersed among diverse structural domains with multifunctional activities. Our prior studies found that the RBD2 and RBD3 of Ranbp2 control mitochondrial motility independently of Ran-GTP-binding in cultured cells, whereas loss of Ran-GTP-binding to RBD2 and RBD3 are essential to support cone photoreceptor development and the survival of mature retinal pigment epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In light of the findings that Ranbp2 controls the activation of kinesin-1, which is the primary motor for mitochondrial transport [254,[328][329][330], it will be important to define the role of this nuclear sequestered Ranbp2 isoform in mitochondrial transport and motor behavior. In this regard, a novel and small isoform of Ranbp2 that co-purifies and colocalizes with the mitochondria has been recently identified [331]. Finally, hnRNPA2B1 is a substrate for the cyclophilin domain (CY) of Ranbp2 and its cis-trans peptidyl-prolyl isomerase (PPIase)/chaperone activity [239].…”
Section: Heterogeneous Nuclear Ribonucleoproteins (Hnrnps)-mutationsmentioning
confidence: 99%
“…In light of the findings that Ranbp2 controls the activation of kinesin-1, which is the primary motor for mitochondrial transport [254,[328][329][330], it will be important to define the role of this nuclear sequestered Ranbp2 isoform in mitochondrial transport and motor behavior. In this regard, a novel and small isoform of Ranbp2 that co-purifies and colocalizes with the mitochondria has been recently identified [331]. Finally, hnRNPA2B1 is a substrate for the cyclophilin domain (CY) of Ranbp2 and its cis-trans peptidyl-prolyl isomerase (PPIase)/chaperone activity [239].…”
Section: Heterogeneous Nuclear Ribonucleoproteins (Hnrnps)-mutationsmentioning
confidence: 99%
“…Apart from an 80 kDa predicted isoform in mitochondria (Patil et al, 2017), no other Nup358 isoform has been previously reported. Thus, we aimed to prove that the 230 kDa band observed in our immunoblots represents an isoform of Nup358.…”
Section: Two Isoforms Of Nup358 Protein Are Differentially Expressed mentioning
confidence: 91%
“…How and when these proteins become accessible for ubiquitination is not clearly understood -it is possible that proteins are ubiquitinated prior to their mitochondrial import, although it is unclear whether large Ub moieties would sterically inhibit translocation across import channels. Ub-conjugating enzymes have been observed in mitochondria (Schwartz et al, 1992, Patil et al, 2019, suggesting they might contribute to the ubiquitination of proteins in organello. Mitochondrial function also appears to be regulated by the UPS, as mitochondrial proteins related to energy production, including components of all four complexes of the OXPHOS machinery and the ATP-synthase, are substrates for ubiquitination (Jeon et al, 2007, Lavie et al, 2018.…”
Section: The Ubiquitin Proteasome System In Omm Protein Quality Controlmentioning
confidence: 99%